2006
DOI: 10.1038/sj.onc.1209968
|View full text |Cite
|
Sign up to set email alerts
|

Sustained leukaemic phenotype after inactivation of BCR-ABLp190 in mice

Abstract: Pharmacological inactivation of cancer genes or products is being used as a strategy for therapy in oncology. To investigate the potential role of BCR-ABLp190 cessation in leukaemia development, we generated mice carrying a tetracycline-repressible BCR-ABLp190 transgene. These mice were morphologically normal at birth, and developed leukaemias. Disease was characterized by the presence of B-cell blasts co-expressing myeloid markers, reminiscent of the human counterpart. BCR-ABLp190 activation can initiate leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
0
19
0
2
Order By: Relevance
“…This is supported by experiments with animal models in which expression of BCR-ABLp190 (the oncogene responsible of Ph þ B-ALL) is driven by a tetracycline-inducible promoter. (43) In this system, suppression of the oncogene after this has already been active does not suppress the leukaemia, indicating that the oncogene is necessary for the initiation of the tumour, but not for its maintenance. Similarly, although treatment of BCR-ABLp210 þ chronic myelogenous leukemia patients with the specific inhibitor imatinib mesylate (Gleevec), kills more differentiated progeny and greatly reduces tumour burden, it is unable to cure the disease because Ph þ stem cells are insensitive to the treatment and regenerate the disease.…”
Section: Cscs In Sarcomasmentioning
confidence: 99%
“…This is supported by experiments with animal models in which expression of BCR-ABLp190 (the oncogene responsible of Ph þ B-ALL) is driven by a tetracycline-inducible promoter. (43) In this system, suppression of the oncogene after this has already been active does not suppress the leukaemia, indicating that the oncogene is necessary for the initiation of the tumour, but not for its maintenance. Similarly, although treatment of BCR-ABLp210 þ chronic myelogenous leukemia patients with the specific inhibitor imatinib mesylate (Gleevec), kills more differentiated progeny and greatly reduces tumour burden, it is unable to cure the disease because Ph þ stem cells are insensitive to the treatment and regenerate the disease.…”
Section: Cscs In Sarcomasmentioning
confidence: 99%
“…Boff-p210 is a murine interleukin 3 (IL3) -independent cell line derived from the hematopoietic cell line Baf/3 [38] that expresses BCR/ABL as a tetracycline-regulated transgene ( BCR/ABL expression is constitutive in the absence of tetracycline or doxycycline) [5254]. Boff-p210 was maintained in Dulbecco's Modified Eagle's Medium (DMEM) (Life Technologies) supplemented with 10% fetal bovine serum (FBS) and 1% of penicillin/streptomycin (Life Technologies) in 5% CO 2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…In other study, using the pB-ALL-associated BCR-ABLp190 form in a tetracycline controllable system, it has been shown that inactivation of the oncogene expression, however, does not stop tumor growth once initiated. 33 These inducible transgenic mice suffer from pB-ALL that cannot be rescued by oncogene inactivation or by Imatinib treatment, similarly to what happens in humans, suggesting that the induction of tumorigenesis does not only depends on the oncogene, but also largely on its pattern of expression, and pointing toward a setting in which the oncogene imposes a leukemic stem cell-specific epigenetic context in which oncogene inactivation cannot lead anymore to a reversion of the phenotype. 33 The discrepancies between the results arising from models that are not so dissimilar in their design also highlight and exemplify the importance of defining stringent phenotypic requirements before concluding that a given mouse model actually recapitulates one of several aspects of the pathology in humans.…”
Section: Bcr-abl C Gemmsmentioning
confidence: 99%